On Central Asian Castianeira arnoldii Charitonov, 1946 (Araneae, Corinnidae), earlier known from juvenile specimens - Marusik, Yuri M. (Zootaxa, 2009)
Castianeira Keyserling, 1879 is one of the largest corinnid genera. Currently it contains 131 species (Platnick, 2009) distributed all over the globe except for Australia and adjacent islands. In the Palaearctic Castianeira is restricted to the southern regions with subtropical climate. The northernmost localities lie in the Iberian Peninsula, Israel, Uzbekistan and South Korea. Four Castianeira species are known from juvenile specimens only. One of such species, Castianeira arnoldii Charitonov, 1946, was described from Uzbekistan. While studying some material collected by Alexander V. Gromov in Central Asia I found an adult female together with 3 juvenile specimens of Castianeira. These specimens were collected rather close to the type locality of C. arnoldii. The size and colour pattern of the juvenile specimens fit well the description provided by Charitonov (1946). Therefore I decided to describe the adult female of this species.